Serum C-reactive protein and procalcitonin levels in non-small cell lung cancer patients - Tulek, Baykal; Koylu, Habibe; Kanat, Fikret; Arslan, Ugur; Ozer, Faruk (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study: The basic uses of C-reactive protein (CRP) and procalcitonin (PCT) in clinical practice are in the diagnosis and follow-up of infectious disease. The fact that CRP already achieves high levels in cases with lung cancer, however, limits its diagnostic specificity. Procalcitonin may be an important marker in the differential diagnosis of lung cancer patients who have fever and high CRP levels. Our objective in this study was to determine the levels of CRP and PCT in patients with newly diagnosed non-infectious non-small cell lung cancer (NSCLC) and to relate these results to patient and disease characteristics. Material and methods: Serum CRP and PCT levels were measured in 79 histopathologically proven NSCLC patients and 20 healthy controls. Results were compared with demographic and clinical variables in patients with NSCLC. Results : Serum CRP concentrations were significantly higher in NSCLC patients compared to the control group [38.30 (7.79–185) mg/dl vs. 7.79 (3.36–26.10) mg/dl; p 0.05). A mild, positive correlation was found between CRP level and tumor diameter. When comparing CRP levels in the lung cancer patients grouped according to age, sex, smoking status, clinical TNM staging and performance status (PS), the only significant difference found was that for PS score. Conclusions : High serum CRP levels in non-infectious NSCLC patients are mainly related to PS status and weakly to tumor size. Adding serum PCT measurement may contribute to exclusion of infections in patients with NSCLC.